Forensic criminology - Williams, Andrew (Routledge, 2015)
"This text provides an examination of the aetiological development of forensic criminology within the UK. It links the subjects of scientific criminology, criminal investigations, crime scene investigation, forensic science and the legal system, and provides an introduction to the important processes that take place from crime scene to courtroom. These processes help identify, define and label the 'criminal' and are crucial for understanding any form of crime within society. The book includes sections on: the epistemological and ontological philosophies of the natural sciences,the birth of scientific criminology and its search for the criminal 'body', the development of early forms of forensic science and crime scene investigation,investigating crime, information, material and evidence, crime analysis and crime mapping, scientific support and crime scene examination,forensic science and detection methods and forensics in the courtroom. The text consists of a mix of historical research and contemporary criminal justice process chapters that provide an introduction to the most common forensic practices, procedures and uses that enable the identification and successful prosecution of criminals. Forensic Criminology provides a framework for understanding the varieties of information work that exist within current criminal justice practice. Forensic Criminology will be essential for students of criminology, criminal justice, criminal investigations and crime science. It will also be useful to those criminal justice practitioners wishing to gain a more in-depth understanding of the links between criminology, criminal investigations and forensics techniques. "--